The Relationship Between Physical Activity Among Adolescent Girls and Primary Dysmenorrhea at SMA Negeri 1 Siak - Okrianti, Surisna; Zuliyana, Zuliyana; Romlah, Siti; Fadhilah, Nadiah (Indonesian Research Journal on Education, 2025)
Primary dysmenorrhea is a common complaint experienced by adolescent girls, often interfering with daily activities, including school-related activities. This study aimed to identify the relationship between physical activity and the intensity of menstrual pain among adolescent girls at SMA Negeri 1 Siak, Siak Regency, in 2025. Physical activity is known to have positive effects in reducing dysmenorrhea symptoms; however, studies on this issue among Indonesian adolescents remain limited. This study employed a quantitative design using a survey approach involving 100 adolescent female respondents selected randomly. Data were collected using questionnaires that measured the frequency of physical activity and the intensity of menstrual pain using the Visual Analog Scale (VAS). The results showed a significant negative relationship between the level of physical activity and menstrual pain intensity (r = -0.35, p < 0.05). Adolescent girls who engaged in regular physical activity reported lower levels of menstrual pain compared to those who were less physically active. These findings suggest that increasing physical activity may serve as an effective strategy for reducing dysmenorrhea symptoms among adolescent girls. Further research is needed to explore other factors that may contribute to this relationship.